The psychological effects of bullying behavior on mental health status among adolescents at secondary school - Abdalhadi Hasan; Amal Alsulami; Bedour Obaid Albadrani; Aziza Ghazi Babear; Alrashidi Mohammed Shadad; Mohammed Mosaaed Aljohani; Khalid Mukhlid Hamad Almutairi; Budour Shudayyid Almutairi (Alexandria Journal of Medicine)
Introduction Bullying among schoolchildren involves the repetition of harmful actions where there are power imbalances between the individuals involved. The psychological effects of bullying were investigated and it was established that bullying is related to symptoms of mental health issues such as selfharm, suicidal thoughts, depression, and anxiety.Objective The study aimed to assess the psychological effects of bullying behavior on the mental health status (depression and stress, and anxiety) of adolescents in secondary schools.Methods The study employed a descriptive crosssectional research design. The study utilized a convenience sampling method, with a sample size of 304 students. The study was conducted at AlArab International Schools and Dar Jana International Schools located in XX, XX. For data collection, the researcher employed different sets of questionnaires, including the Demographic Questionnaire, the Revised Olweus Bully/Victim Questionnaire (ROBVQ), and the Depression Anxiety Stress Scales21 [DASS21).Findings The results indicate that there is a significant difference in the psychological effects of bullying behavior on depression and stress, but not on anxiety. Additionally, it suggests that sociodemographic variables are associated with bullying frequencies and impacts on the mental health status of the victims.Conclusions The present study has revealed that there is a significant difference in the psychological effects of bullying behavior on depression and stress, but not on anxiety. The sociodemographic variables have been exposed to bullying frequencies and impacts on the mental health status of the victims.